2010
DOI: 10.1508/cytologia.75.37
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Chromosome Associations in Uraria picta (Jacq.) DC (Family: Leguminosae)

Abstract: SummaryThe meiocytes of Uraria picta (Jacq.) DC (Family: Leguminosae; Papillionoide; annual medicinal herb) had nϭ11 chromosomes with an average chromosomal association of 0.11 IVϩ10.29 IIϩ0.98 I per cell at diakinesis and metaphase I. The bivalents formed rods (rods: 1-11/cell, 6.95Ϯ0.22; rings: 0-9/cell, 3.59Ϯ0.25/cell) mostly at MI with mean chiasma of 14.22Ϯ 0.24 (8 to 20) per cell. Formation of 11 II in PMCs was predominant (62.71%). About 11.25% of the cells had a ring quadrivalent. All AI cells were cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…of West Bengal, India; moisture content 11.6%; treated with ethyl methane sulphonate (EMS), diethyl sulfate (dES) and hydroxylamine (HA); treatments: 0.25%, 0.50% and 1.00% for 3 and 6 h durations each), a dwarf plant (1.00% EMS, 6 h; 0.16% over the M 2 mutant population) possessing 100.0% sterile pollen grains (assessed following 1.0% acetocarmine staining technique, (Marks 1954); fully stained pollen grains were considered fertile) was screened. Meiotic configurations assessed (as suggested by Bhattacharya and Datta 2010a) in the marked plant were cytologically normal and alike to control. The male sterile plant formed pods (grey pods yielded viable seeds and black pods set nonviable seeds (Bhattacharya and Datta 2010b)) and set viable seeds on open pollination (controlled pollination is rather difficult due to its reproductive biology), thereby indicating female fertility of the marked plant.…”
Section: Methodsmentioning
confidence: 78%
“…of West Bengal, India; moisture content 11.6%; treated with ethyl methane sulphonate (EMS), diethyl sulfate (dES) and hydroxylamine (HA); treatments: 0.25%, 0.50% and 1.00% for 3 and 6 h durations each), a dwarf plant (1.00% EMS, 6 h; 0.16% over the M 2 mutant population) possessing 100.0% sterile pollen grains (assessed following 1.0% acetocarmine staining technique, (Marks 1954); fully stained pollen grains were considered fertile) was screened. Meiotic configurations assessed (as suggested by Bhattacharya and Datta 2010a) in the marked plant were cytologically normal and alike to control. The male sterile plant formed pods (grey pods yielded viable seeds and black pods set nonviable seeds (Bhattacharya and Datta 2010b)) and set viable seeds on open pollination (controlled pollination is rather difficult due to its reproductive biology), thereby indicating female fertility of the marked plant.…”
Section: Methodsmentioning
confidence: 78%
“…Hirayoshi (1957) disagreed with the hypothesis which considers the involvement of homologous chromosome in secondary association and after examining careful results in Oryzeae and Zizanieae gave the conclusion that the secondary association may be a phenomenon operating under bio-and physico-chemical reactions and has no relation to the true homology of chromosomes. Secondary pairing between bivalents has been considered as an indicator of polyploid nature of a species as reported in Ocimum (Mukherjee and Datta, 2005), and Uraria picta (Bhattacharya and Datta, 2010). According to Stebbins (1950), secondary association can be considered a phenomenon which depicts the polyploid nature of a species or genus, but elaborate phylogenetic predictions cannot be drawn from this as the secondary pairing between bivalents is considerably modified by other chromosomal changes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Stebbins (1950), secondary association can be considered a phenomenon which depicts the polyploid nature of a species or genus, but elaborate phylogenetic predictions cannot be drawn from this as the secondary pairing between bivalents is considerably modified by other chromosomal changes. But amidst these explanations, Bhattacharya and Datta (2010) concluded that no inferences should be drawn regarding the polyploidy origin of species solely on the basis of secondary pairing. As an alternative, the cytological data must be co-related with locus specific molecular markers using FISH (Fluorescent in situ hybridization) to get a precise decision (Litcher, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, it is often encountered in meiotic processes of different plant species in tracing basic chromosome numbers and the polyploid nature of the species (Kempanna and Riley 1964, Gupta and Roy 1973, Agarwal 1983, Sengupta and Datta 2003, Mukherjee and Datta 2005, Iqbal and Datta 2007, Das et al 2009, Bhattacharya and Datta 2010, Mandal and Datta 2011, Halder et al 2012, Kumar and Singhal 2013. The present investigation describes meiotic configurations documenting secondary chromosome association in Indigofera tinctoria L. (Family: Fabaceae), an annual, biennial, or perennial shrub, based on the climate under which it is grown (Gaboriaud- Kolar et al 2014).…”
mentioning
confidence: 88%